2007
DOI: 10.1111/j.1751-1097.2007.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Power Laser Irradiation on Intracellular Calcium and Histamine Release in RBL‐2H3 Mast Cells

Abstract: Although laser irradiation has been reported to promote skin wound healing, the mechanism is still unclear. As mast cells are found to accumulate at the site of skin wounds we hypothesized that mast cells might be involved in the biological effects of laser irradiation. In this work the mast cells, RBL-2H3, were used in vitro to investigate the effects of laser irradiation on cellular responses. After laser irradiation, the amount of intracellular calcium ([Ca2+]i) was increased, followed by histamine release,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 34 publications
1
58
0
1
Order By: Relevance
“…Photodamage during microscopy indeed indicates that cells can be stimulated solely by photons. Along with this idea, it was found that low energy visible light irradiation with about 0.1 mw/cm 2 power density for seconds to minutes could induce changes of intracellular Ca 2+ concentrations in macrophages [76], sperms [77][78][79], lymphocytes [80], skeletal muscle cells [81,82], human fibroblasts [83] and mast cells [84]. The cellular Ca 2+ level slowly increased during continuous laser irradiation and could maintain for minutes.…”
Section: All-optical Stimulationmentioning
confidence: 98%
“…Photodamage during microscopy indeed indicates that cells can be stimulated solely by photons. Along with this idea, it was found that low energy visible light irradiation with about 0.1 mw/cm 2 power density for seconds to minutes could induce changes of intracellular Ca 2+ concentrations in macrophages [76], sperms [77][78][79], lymphocytes [80], skeletal muscle cells [81,82], human fibroblasts [83] and mast cells [84]. The cellular Ca 2+ level slowly increased during continuous laser irradiation and could maintain for minutes.…”
Section: All-optical Stimulationmentioning
confidence: 98%
“…Such mechanical forces may stimulate cutaneous mast cells, which are the main effector cells involved in allergic reactions and innate immunity, initiating chain physiological reactions (Malaviya and Georges, 2002). Mast cells can react quickly to an external stimuli, including physical ones like shear stress (Yang et al, 2009), light (Yang et al, 2007), UVA ) rays and heat (Wu et al, 2012) to initiate a physiological chain reaction, such as increment of [Ca 2+ ] c (cytosolic calcium concentration) and the degranulation, then release histamine and substance P, which give rise to vasodilatation, vessel permeability increment and microcirculation improvement. Therefore mast cells could be the targeting cells of the mechanical stimuli to recuperate the physiological function of bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Zum blauen Laser gibt es generell bislang noch sehr wenige Studien im Bereich der Medizin. Neben Forschungen auf zellulärer Ebene in Shanghai [9] beschäftigen sich auch Wissenschafter in New York [10], Finnland [1], Deutschland [4] und Japan [11,12] mit der Thematik. Der Ansatz, den blauen Laser in der Akupunktur zu verwenden, ist neu und liefert offensichtlich trotz geringer Eindringtiefe (blau: 1-2 mm vs. rot und infrarot: 2-3 cm) Effekte, die noch näher untersucht werden sollten [5][6][7].…”
Section: Introductionunclassified